Cross-listing and the scope of the firm - Peng, Mike; Su, W. (Pergamon, 2014)
"What determines the scope of the firm?" is one of the most fundamental questions in strategic management and international business. Yet no previous research has investigated the relationship between the scope of the firm and cross-listing-a firm listing its stock on overseas exchanges. We leverage the resource-based and institution-based views with a focus on cross-listed firms from emerging economies. We predict that cross-listing may result in a narrower product scope in the short run, a wider product scope in the long run, an expanded geographic scope overall, and a higher propensity to engage in mergers and acquisitions in the host country.